Meso-instituições e o desempenho da cadeia produtiva do leite na fronteira oeste do Rio Grande do Sul - Cordeiro, Márcio Pereira (2021)
The dairy farming has significant participation in the economy of Rio Grande do Sul and had strong expansion in Brazil in recent years, so it demanded new standards to qualify the milk production and ensure competitiveness in foreign markets. Therefore, the activity suffers pressure from formal macro-institutions, which can influence the heterogeneity of the sector's performance in the various regions, currently the Normative Instructions No. 76 and 77 govern them. On the other hand, one of the main research frontiers in New Institutional Economics is the concept of meso-institutions, an intermediate institutional layer that aims to act as an interface mechanism between the organizational arrangements (micro-institutions) and the rules of the game of the sector (macro-institutions). Thus, it is relevant to identify the functionality and influence of meso-institutions on the performance of the dairy supply chain. The aim of this study is to analyze meso-institutions and their influence on the performance of dairy basins in the Fronteira Oeste of Rio Grande do Sul. To this end, the study is of exploratory-descriptive type, with a mixed approach. The collection techniques adopted were: documentary research, interviews, self-reports, and questionnaires with a sample of 96 milk producers. The qualitative data were treated by interpretative analysis, and the quantitative data were analyzed by the Mann-Whitney test and multiple linear regression. The results identified the meso-institutions and their functions of translation, implementation, and monitoring of rules. The test showed that the performance of the institutions is not similar among the basins regarding the translation and implementation of rules. From the regression results it was found that an effective monitoring, when the parameters established by the regulations are followed by the mesoinstitutions, positively influences the perception of the producer's performance. Therefore, to maintain the competitiveness of the sector, it is necessary to have an agent capable of translating, implementing and monitoring the rules in the organizational arrangement, called meso-institution, so that the general rules are taken to the micro level with less impact. In view of this, it is necessary to expand the research on the institutions that amortize, and thus provide subsidies to public policies for the consolidation of the milk activity, especially the importance that should be given to meso-institutions, as interlocutors with the macro level and the economic and social problems of producers.